Reactions to Provocation and Beliefs About Aggression in an Indian Sample - Thanzami, VanLal; Archer, John (International Journal of Conflict and Violence (IJCV), 2013)
Western studies have found that men tend to view their aggression as instrumental whereas women tend to view it in expressive terms. A preliminary qualitative study on an Indian sample found low internal consistency for these measures, and that men viewed their aggression in both instrumental and expressive terms. The present study used scenarios to examine feelings about aggression in 300 males and females in India, aged 16 and 26 years. Males were more likely to view aggression in terms of loss of control, shame for family, and acceptability, while 16-year-olds were more likely to feel shame and embarrassment following aggression. These robust findings indicate that for this sample feelings about aggression are more complex than the two constructs, instrumental and expressive, can capture.